2016
DOI: 10.18632/aging.100991
|View full text |Cite
|
Sign up to set email alerts
|

Aging of mice is associated with p16(Ink4a)- and β-galactosidase-positive macrophage accumulation that can be induced in young mice by senescent cells

Abstract: Senescent cells (SCs) have been considered a source of age-related chronic sterile systemic inflammation and a target for anti-aging therapies. To understand mechanisms controlling the amount of SCs, we analyzed the phenomenon of rapid clearance of human senescent fibroblasts implanted into SCID mice, which can be overcome when SCs were embedded into alginate beads preventing them from immunocyte attack. To identify putative SC killers, we analyzed the content of cell populations in lavage and capsules formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
290
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(297 citation statements)
references
References 77 publications
7
290
0
Order By: Relevance
“…Beads that elaborate SASP-components attract macrophages, which show some features of senescence (e.g. SA-β-gal and p16 INK4a expression) (Hall et al, 2016). It is likely that some bone marrow-derived cells found in nascent neoplasms or after UV injury are also p16 INK4a –expressing macrophages (Burd et al, 2013; Sorrentino et al, 2014a), and these cells may accumulate with aging.…”
Section: Roles Of Senescence In Health and Diseasementioning
confidence: 99%
“…Beads that elaborate SASP-components attract macrophages, which show some features of senescence (e.g. SA-β-gal and p16 INK4a expression) (Hall et al, 2016). It is likely that some bone marrow-derived cells found in nascent neoplasms or after UV injury are also p16 INK4a –expressing macrophages (Burd et al, 2013; Sorrentino et al, 2014a), and these cells may accumulate with aging.…”
Section: Roles Of Senescence In Health and Diseasementioning
confidence: 99%
“…Studies have shown that the genetic clearance of SCs extends the lifespan of mice and delays the onset of several age-associated diseases in both progeroid and naturally-aged mice [1215]. It has also been shown that rapamycin and metformin increase lifespan in mice and marmoset monkeys, by suppressing the induction of senescence [1620].…”
Section: Introductionmentioning
confidence: 99%
“…However, when Hall and co-authors analyzed the adipose tissue of old mice for SCs before and after clodronate treatment, they found a large reduction in β-gal+ cells. In addition, most β-gal+ cells expressed F4/80, a well-known and widely used marker of murine macrophage populations, thus reinforcing the notion that most SCs accumulating in fat during aging are a macrophage subset, rather than pre-adipocytes [4]. …”
mentioning
confidence: 79%
“…Now, Hall and co-workers have demonstrated that SCs can spread senescence to immune cells [4]. By implanting into the peritoneal cavity of SCID mice senescent fibroblasts capable of releasing a small bioluminescent protein, the authors showed that acquired immunity is not mandatory for SC clearance.…”
mentioning
confidence: 99%
See 1 more Smart Citation